(untitled) (Research, Society and Development, 2021)
Tongue-tie or ankyloglossia, is a condition whereby the lingual frenulum attaches near the tip of the tongue and may be short, tight and thick. Tongue-tie has been cited as a cause of poor breastfeeding and maternal nipple pain. Frenectomy, which is commonly performed, may correct the restriction to tongue movement and allow more effective breastfeeding with less maternal nipple pain. Traditionally, surgical intervention is performed using a scalpel, however in the last years there has been an important advent of using lasers in this procedure. Objective: carry out a systematic review on the use of lasers as therapy for ankyloglossia. Methods: systematic review of randomized clinical studies with a score ≥ 6 on the PEDro scale (Physiotherapy Evidence Database) published in the databases including PubMed, Cochrane and SciELO. Studies that evaluated the use of laser in the treatment of children with ankyloglossia were selected. Results: In total, 7 studies using laser (Diode or CO2) as one of the techniques for frenectomy were analyzed. In 401 patients underwent lingual frenectomy the benefit between performing the laser technique over the traditional scalpel technique is clearly described. Conclusion: Frenectomy surgery using lasers provides a more efficient and comfortable treatment for the child patient compared to traditional scalpel/blade methods. However, there is no consensus or evidence to indicate the type of laser to be used.